2009
DOI: 10.1017/s0959259809990359
|View full text |Cite
|
Sign up to set email alerts
|

Serum phosphate in older people

Abstract: SummaryPhosphate (PO4−) has a number of important functions in the human body and abnormalities of phosphate handling and phosphate levels are common in older people. We review the physiological functions of phosphate, the effects of phosphate deficiency and excess, and discuss the evidence underpinning management of these conditions in older people. Both hyper- and hypophosphataemia have been associated with a variety of adverse effects in different patient groups. There is currently little evidence to guide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In the review of the literature, abnormalities of phosphate handling and phosphate levels were common in older people and were clinically important in some cases. 19 As well as in specific diseases or conditions, it was reported that serum phosphate (s-phosphate) levels were associated with in-hospital mortality in general hospitalized patients. 20 The level of s-phosphate is one of the most commonly assessed serum measures in hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the review of the literature, abnormalities of phosphate handling and phosphate levels were common in older people and were clinically important in some cases. 19 As well as in specific diseases or conditions, it was reported that serum phosphate (s-phosphate) levels were associated with in-hospital mortality in general hospitalized patients. 20 The level of s-phosphate is one of the most commonly assessed serum measures in hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study by Scragg et al, it was found that low serum 25(OH)D levels are associated with increased heart rate, systolic blood pressure, and RPP. It was also suggested that low vitamin D status may increase cardiac work in 27,153 participants aged ≥20 years, in the National Health and Nutrition Examination Surveys (NHANES) carried out from 1988 to 1994 and from 2001 to 2006 [47] . Our findings are completely in favor of the two reports.…”
Section: Introductionmentioning
confidence: 99%